Unilateral absence of pulmonary artery complicated by asymmetric sarcoidosis - Mandeep Singh; Dilbag Singh; Avneet Boparai; Gaganpreet Singh; Sunil K. Chhabra (The Egyptian Journal of Bronchology)
Abstract Unilateral absence of pulmonary artery (UAPA) is a rare congenital anomaly which may be diagnosed in childhood or discovered incidentally later in adulthood with symptoms of coexistent/superadded disease. Herein, we are describing a case of a 40-year-old female patient who was found to have UAPA along with noncaseating granulomatous inflammation of mediastinal lymph nodes as well as lung tissue consistent with sarcoidosis, on the side of the absent pulmonary artery. This case report highlights the importance of accurate diagnosis of a potentially treatable disease in the settings of a congenital disease.